Interplay of kidney function and anti-SARS-CoV-2 antibodies in COVID-19 mortality: a prospective cohort study - Sylvia Mink; Heinz Drexel; Andreas Leiherer; Janne Cadamuro; Wolfgang Hitzl; Emanuel Zitt; Matthias Frick; Patrick Reimann; Christoph H. Saely; Peter Fraunberger (Scientific Reports)
Abstract CKD has been recognized as an independent risk factor for severe disease and death in COVID-19. Given the high variability in humoral responses, their general decrease in strength, quality, and durability with age, and the decline of antibody levels over time, personalized vaccination regimes would ensure optimal protection of patients with CKD. This prospective, multicenter cohort study included 1112 hospitalized COVID-19 patients from five study centers. Anti-SARS-CoV-2-spike antibodies and eGFR were measured on hospital admission. The primary outcome was all-cause in-hospital mortality. Reduced kidney function combined with anti-SARS-CoV-2 spike antibody levels was a stronger predictor of COVID-19 mortality than either parameter separately. After adjusting for potential confounders, patients with an eGFR of 60–89 ml/min, 30–59 ml/min, and < 30 ml/min had 4.5, 8.5, and 8.4 times higher odds of dying if antibody levels were below the Youden index of 182BAU/ml (aOR 4.468, 95%CI 1.599–12.486, p = 0.004; 8.528, 3.190–22.793, p < 0.001; 8.400, 2.571–27.442, p < 0.001). Mortality rates did not differ significantly by renal function in CKD patients with antibody levels > 1200BAU/ml. In patients with impaired kidney function, survival is strongly associated with sufficiently high antibody levels. Additional booster vaccinations should be considered in CKD patients with antibody levels < 1200BAU/ml.